Strategic adaptation and the value of forecasts: The development of a conceptual framework - Yusof, Faizal Mohamed; Aziz, Rozainun Abdul (Journal of Business Economics and Management, 2008)
This paper examines the lack of emphasis on the value of forecasts in strategic adaptation frameworks. The objective of this paper is to offer a conceptual framework of strategic adaptation that incorporates and emphasizes the value of forecasts. In developing the framework, we incorporate three different studies. Eunni's model (2003) purports to rank companies with high strategic adaptation ability in an industry. Further, in developing our framework, we specifically link the contributions of Lawrence et al. (2006) and Mentzer et al.(1996, 1999). Our study highlights that companies with high strategic adaptation ability need to be examined further in order to understand and take on board how they withstand the volatile market. It is intended that the conceptual framework, driven by previous studies and the current scenario, will offer a better direction for companies to adapt towards an objective indicator of the value of forecasts for strategic purposes.First published online: 14 Oct 2010